2022
DOI: 10.3390/women2030024
|View full text |Cite
|
Sign up to set email alerts
|

Microcredit Membership and Self-Reported Healthcare Autonomy among Bangladeshi Women

Abstract: Participation in microcredit programs has so far received widespread research and policy attention in the context of health and empowerment among Bangladeshi women. However, not much is known regarding the relationship between participation in microcredit programs and healthcare autonomy (HA) among women. In the present study, we analyzed two nationally representative surveys (Bangladesh Demographic and Health Survey 2004 and 2014), to assess the relationships between MC membership and HA among adult women (n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Earlier research on post-nuptial continuation of education among women in Bangladesh mainly focused on some individual-level variables, such as age at marriage, childbirth, owning a cell phone, or better sanitary conditions 27 28. Bhowmik et al revealed that women who married before age 18 and adolescent mothers were less likely to continue education after marriage 27.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier research on post-nuptial continuation of education among women in Bangladesh mainly focused on some individual-level variables, such as age at marriage, childbirth, owning a cell phone, or better sanitary conditions 27 28. Bhowmik et al revealed that women who married before age 18 and adolescent mothers were less likely to continue education after marriage 27.…”
Section: Introductionmentioning
confidence: 99%